Family Interaction and Consensus with IT Support - Peter Karlsudd (International Journal of Telemedicine and Applications)
Experience shows that there are great defects in information and collaboration between families and professionals in the health and care sector. In an attempt to improve the quality of the efforts planned and implemented in collaboration with relatives a family-related IT-based collaboration system called CIDC was constructed. With the intention to facilitate communication, information, documentation, and collaboration the system was tested together with parents of children with cognitive impairment. The system contains a number of functions gathered in a so-called e-collaboration room. The person administering and distributing the system authorizes the patient/care recipient or relative to build up an e-collaboration room. The result has been largely positive, but the part, which was supposed to document everyday activities, leaves much to be desired. For this reason a follow-up study was completed, and an iPad was used as a contact book, which with the help of the Dropbox software provided increased insight into the child and improved the contact with parents without losing confidentiality or causing extra workload for the staff. By automatic download from the iPad parents and/or contact persons could easily follow the documentation of children’s everyday activities.